2020
DOI: 10.1101/2020.04.25.061176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancing KCC2 activity decreases hyperreflexia and spasticity after chronic SCI

Abstract: After spinal cord injury (SCI), the majority of individuals develop spasticity, a debilitating condition involving involuntary movements, co-contraction of antagonistic muscles, and hyperreflexia. By acting on GABAergic and Ca2+-dependent signaling, current anti-spastic medications lead to serious side effects, including a drastic decrease in motoneuronal excitability which impairs motor function and rehabilitation efforts. Exercise, in contrast, decreases spastic symptoms without decreasing motoneuron excitab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 86 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…Improvements in spasticity-like symptoms have also been reported (Boulenguez et al, 2010). When a KCC2 activator was administered to rats with spinal cord lesions, it was found that the expression of KCC2 was up-regulated in the membranes of motor neurons of the lumbar enlargement, and the spasticity symptoms were alleviated (Bilchak et al, 2021). Body Weight-Supported Treadmill training can also up-regulate KCC2 through the trkB pathway, regulating spinal cord excitability and reducing spasticity .…”
Section: Kcc2/nkcc1 and Spasticity After Spinal Cord Injurymentioning
confidence: 77%
See 2 more Smart Citations
“…Improvements in spasticity-like symptoms have also been reported (Boulenguez et al, 2010). When a KCC2 activator was administered to rats with spinal cord lesions, it was found that the expression of KCC2 was up-regulated in the membranes of motor neurons of the lumbar enlargement, and the spasticity symptoms were alleviated (Bilchak et al, 2021). Body Weight-Supported Treadmill training can also up-regulate KCC2 through the trkB pathway, regulating spinal cord excitability and reducing spasticity .…”
Section: Kcc2/nkcc1 and Spasticity After Spinal Cord Injurymentioning
confidence: 77%
“…Then, activating downstream signaling pathways and regulating KCC2/NKCC1 expression, and effectively improve the spasticity and pain after SCI (Tashiro et al, 2015). And this effect can be inhibited by the BDNF blocker TrkB-IgG, suggesting that activation of BDNF is critical to relief from spasticity and pain symptom after SCI (Bilchak et al, 2021).…”
Section: Kcc2/nkcc1 and Neurodevelopmentmentioning
confidence: 99%
See 1 more Smart Citation